From Mosques and Coffeehouses to Squares and Cafés: the Production and Transformation of Political Public Spaces and Social Life in Modern Tehran - (:unkn) unknown (My University, 2016)
Why did the spaces of protest in Tehran, the capital of Iran, shift from sacred spaces of the city, two mosques and a holy shrine during the 1905 and 1906 Constitutional Revolution, to the streets and squares of the northern city in the 1940s and the early 1950s? Through extensive archival research in Iran, including examination of old Iranian periodicals, memoirs, travelogues, maps, and the like, I found that this spatial transformation was the tip of an iceberg; it was closely related to the transformations of urban society, social life, and social spaces in Tehran that had been brewing for decades. Nineteenth-century Iranian urban society was largely a classless society; it consisted of numerous smaller communities. Social life and the social spaces of Tehran –takīyyihs, zūrkhānihs, mosques, bathhouses, and coffeehouses –were highly shaped by communal identities. In this context, the main sacred spaces of the city were the only sites that could transcend communal diversities and brought people together for a common political cause. However, Iranian urban society underwent massive transformations during the first half of the twentieth century. Two new urban classes, the modern middle and the urban working classes, developed in Iranian cities, particularly Tehran, which were free from the bonds of communal life. The city’s social spaces and social life transformed alongside urban society. A new spatial discourse that was incubated in Iranian society for a century became the main force transforming Iranian cities, particularly Tehran. Moreover, new types of social spaces after European models –cinemas, theaters, cafés, restaurants, and sport clubs –became the centers of social life for the modern middle class. This class became the main political social force in the city. It rejected traditional and religious spaces and defined a new way of life for itself. In this context, the newly built network of streets and squares of the northern section of Tehran substituted the sacred spaces of the city as the primary political public spaces. Alongside the main historical element of the dissertation, there is also a theoretical deliberation. Through the examination of various instances of social movements and their social forces, I investigate the relationship between the public sphere and political public spaces in a context beyond the conventional geographic scope of western urban and political theories. My research suggests that the current models of the public sphere, including Habermas’s bourgeois public sphere, do not map onto Iranian society. Instead, my research suggests a new model based on the particularities of Iranian urban society during the nineteenth and the early twentieth centuries, but potentially applicable to cases far beyond Tehran as well. In this model, I introduce the communal sphere as the main construct of segmented Iranian urban society in the nineteenth century, mediated between the private and public spheres. In this context, the public sphere formed as the outcome of coming together of various communal spheres through the binding force of religion and political activities of a new urban bourgeoisie, the propertied middle class, at the turn of the twentieth century. Also, I found that the public sphere and political public spaces are deeply interconnected; they share certain commonalities that can be investigated through the socio-historical analysis.
Keywords: Communal Sphere; Iran; Political Public Space; Public Sphere; Social Movement; Tehran